1989
DOI: 10.1111/j.1349-7006.1989.tb02258.x
|View full text |Cite
|
Sign up to set email alerts
|

Inductions of Ornithine Decarboxylase and Replicative DNA Synthesis but not DNA Single Strand Scission or Unscheduled DNA Synthesis in the Pyloric Mucosa of Rat Stomach by Catechol

Abstract: The possible tumor‐promoting and genotoxic activities of catechol were examined. Administration of catechol by gastric intubation at doses of 10 to 90 mg/kg body weight to male F344 rats induced up to 19‐fold increase in ornithine decarboxylase activity with a maximum after 8 h and up to 8‐fold increase in replicative DNA synthesis with a maximum after 24 h in the pyloric mucosa of the stomach. These results suggest that catechol has tumor‐promoting activity in the pyloric mucosa of rat stomach. However, its a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

1990
1990
2013
2013

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…3). With the 0.1 °~o dose, erosion was observed from 12 hr to day 3, but no remarkable changes were evident on day 7. The thickness of the prepyloric region of the glandular stomach epithelium initially increased at day 1 in the 1 and 0.5% groups and at day 2 in the 0.1 % group.…”
Section: Sequential Morphological Changesmentioning
confidence: 86%
See 1 more Smart Citation
“…3). With the 0.1 °~o dose, erosion was observed from 12 hr to day 3, but no remarkable changes were evident on day 7. The thickness of the prepyloric region of the glandular stomach epithelium initially increased at day 1 in the 1 and 0.5% groups and at day 2 in the 0.1 % group.…”
Section: Sequential Morphological Changesmentioning
confidence: 86%
“…Erosion/ulcer continued to be present for 7 days, but inflammatory cell infiltration gradually decreased with time. In the early stage, small, focal, and multiple superficial erosions were found throughout the pyloric region, but they became preferentially localized at the prepylorus on day 7 (Fig. 3).…”
Section: Sequential Morphological Changesmentioning
confidence: 99%
“…Kawanishi et al (1989) reported that Pyrocatechol did not induce DNA cleavage. Unscheduled DNA synthesis was induced by Pyrocatechol in three studies with MRC-Wistar rats (Mirvish et al, 1985), but one study with F344 rats was negative (Furihata et al, 1989). Pyrocatechol inhibited DNA synthesis by 65% in mouse lymphoma cells (PellackWalker et al, 1985) and by 52% in bone marrow cells (Lee et al, 1989) but had no effect upon a cell-free DNA synthetic system (Lee et al, 1989) or bladder epithelial cells from rats (Kurata et al, 1990).…”
Section: Mutagenicitymentioning
confidence: 96%
“…Negative results were obtained in studies with supercoiled <})X-174 DNA (Lewis et al, 1988b) an mouse lymphoma cells (Pellack-Walker and Blumer, 1986). Also, no increase in single-strand scission was observed in DNA of the gastric pyloric mucosa of rats administered Pyrocatechol by gastric intubation (Furihata et al, 1989). Kawanishi et al (1989) reported that Pyrocatechol did not induce DNA cleavage.…”
Section: Mutagenicitymentioning
confidence: 96%
“…The time-dependency of ODC activity induction in the pyloric mucosa by taurocholate, NaCl, catechol, K2S2O5, formaldehyde and glyoxal was transient and reached a maximum after 4 h by taurocholate (72), 6-9 h by NaCl (78) and catechol (63), and 16 h by glyoxal (68), formaldehyde (80) and K2S2O5 (81). ODC activity returned to the control level within 48 h after administration of these compounds (57).…”
Section: Attempts At Organ-speciˆc In Vivo Short-term Assays For the mentioning
confidence: 97%